The influences of audit fees, competence, independence, auditor ethics, and time budget pressure on audit quality - Neni Meidawati; Arden Assidiqi (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2019)
This study aims to determine the effects of audit fees, auditor’s competence, independence, and ethics, as well as time budget pressure on audit quality. This research used quantitative method. The population was the auditors who worked in Accounting Firms in Semarang City, Indonesia. The sampling technique was simple random sampling with 45 respondents. The data were collected by distributing the questionnaires to several auditors working at the accounting firms. The data were analyzed using multiple regression analysis. The results of this study indicate that the competence, auditor ethics, and time budget pressure had positive effect toward audit quality. Meanwhile, audit fee negatively affected audit quality, and independence had no effect on audit quality.